Leadership of Women Ulama During Pandemic in Pesantren: Study in Kebon Jambu Ciwaringin and Al-Baqaroh Lirboyo - Fitrotul Muzayanah; Dewi Anggraeni (POTENSIA: Jurnal Kependidikan Islam, 2023)
This study aims to analyze the leadership of Women Ulama as Nyai Pesantren during the pandemic. This research was conducted in two Pesantren led by women, Nyai Hannah Zamzami in East Java and Nyai Masriyah Amva in West Java. Using qualitative research with a phenomenological approach, researchers revealed how women's leadership could respond to the challenges of the Covid-19 pandemic. Data collection was conducted through in-depth interviews and intense life researchers in Pesantren. The collected data were analyzed comparatively.  The results showed: (1) The typology of the Pesantren has different characteristics. Pesantren, under the leadership of Nyai Masriyah Amva is favored with character education according to talents and interests as well as edupreneurship. Pesantren, under the leadership of Nyai Hannah Zamzami, emphasized more tahfidz al-Qur'an with the Fami Bisyauqin method (2) The type of Nyai leadership in Pesantren Kebon Jambu Babakan Ciwaringin West Java and Pesantren al-Baqarah East Java, both apply democratic, egalitarian, openness leadership types. The difference is that Nyai Masriyah Amva is more dominant with the character of independence, while Nyai Hannah Zamzami is more dominant with a strong character in memorizing the Qur'an. (3) The implications of the leadership types of Nyai Masriyah and Nyai Hannah are very influential on developing Pesantren and human resources, especially during the Covid-19 pandemic. With a democratic, egalitarian, and openness, Pesantren education continues its educational process during a pandemic and innovates by utilizing social medicine as a medium for da'wah.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in Malay Translate to English    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate Malay to EnglishPRO Never translate Malay Never translate ejournal.uin-suska.ac.id